Plated steel material and method for producing plated steel material
By forming an Mg concentrated layer on the plating layer of Zn-Al-Mg alloy-coated steel, the problems of early white rust and oxidation and discoloration of the coating in heavy salt damage areas are solved, and excellent corrosion resistance, processability and discoloration resistance are achieved.
Patent Information
- Application Number
- CN202280099156.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-31
- Filing Date
- 2022-12-16
- Publication Date
- 2025-03-28
AI Technical Summary
In heavy salt damage areas, Zn-Al-Mg-based alloy-plated steel with high Al concentration and Mg concentration is prone to white rust in early stage, and the plating layer with high Mg concentration is prone to oxidation and discoloration, and has poor processability.
A plated steel material with a Zn-Al-Mg alloy layer and an Mg concentrated layer is used. The Zn content in the chemical composition of the plating layer exceeds 65%, the Al content is 5% to 25%, and the Mg content is 3% to 12.5%. A Mg concentrated layer is formed on the surface of the Zn-Al-Mg alloy layer with a thickness of more than 0.8 μm and no more than half the thickness of the plating layer.
Provide excellent corrosion resistance in heavy salt damage areas, while taking into account both processability and discoloration resistance to avoid early white rust and oxidation and discoloration of the coating.
Smart Images

Figure BDA0005271644570000231 
Figure BDA0005271644570000241 
Figure BDA0005271644570000251
Abstract
Description
Technical Field
[0001] The present disclosure relates to a plated steel material and a method for manufacturing the plated steel material. Background Art
[0002] For example, in the field of building materials, a variety of plated steels are being used. Most of them are galvanized steels. In view of the requirement for longer life of building materials, research on improving the corrosion resistance of galvanized steels has been conducted for a long time, and a variety of plated steels have been developed. The first high-corrosion-resistant plated steel used as a building material was Zn-5% Al plated steel (Galfan plated steel) whose corrosion resistance was improved by adding Al to the Zn-based coating. It is a well-known fact that corrosion resistance is improved by adding Al to the coating, and by adding 5% Al, Al crystals are formed in the coating (specifically, Zn phase), thereby improving corrosion resistance. Zn-55% Al-1.6% Si plated steel (Galvalume steel) is also a plated steel with improved corrosion resistance based on basically the same reason.
[0003] Among them, the charm of Zn-based plated steel is the sacrificial anode corrosion protection effect on the base steel. That is, in the cut end surface of the plated steel, the cracked part of the coating during processing, and the exposed part of the base steel due to coating peeling, the coating melts around the base steel before corrosion, and the coating melt components form a protective film. As a result, the base steel can be prevented from rusting to a certain extent.
[0004] Generally speaking, this effect is preferred when the Al concentration is low and the Zn concentration is high. Therefore, in recent years, highly corrosion-resistant plated steels with a relatively low Al concentration of about 5% to 25% have begun to be put into practical use. In particular, plated steels with a relatively low Al concentration and containing about 1% to 3% Mg have better corrosion resistance than Galfan plated steels. Therefore, it has become a market trend for plated steels and is now widely known in the market.
[0005] As such a plated steel material containing a certain amount of Al and Mg, for example, a plated steel material disclosed in Patent Document 1 has been developed.
[0006] Specifically, Patent Document 1 discloses: "A hot-dip Zn-Al-Mg-Si plated steel material, wherein the plated steel material surface having a plated layer has a thickness of 1 mm per 1 mm. 2 There are more than 200 Al phases, and the plating layer contains Al: 5-18 mass %, Mg: 1-10 mass %, Si: 0.01-2 mass %, and the remainder: Zn and inevitable impurities.
[0007] In addition, Patent Document 2 discloses: "A plated steel material comprising a steel material and a plated layer including a Zn-Al-Mg alloy layer disposed on the surface of the steel material, wherein the chemical composition of the plated layer contains Zn: more than 65.0%, Al: more than 5.0% and less than 25.0%, Mg: more than 3.0% and less than 12.5%, and Sn: 0.1% to 20.0%, and Al crystals are present in a backscattered electron image of the Zn-Al-Mg alloy layer obtained by observing the Zn-Al-Mg alloy layer at a magnification of 100 times with a scanning electron microscope after the surface of the Zn-Al-Mg alloy layer is polished to 1 / 2 of the layer thickness, and the average value of the cumulative circumference of the Al crystals is 88 to 195 mm / mm 2 .
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Laid-Open No. 2001-355053
[0011] Patent Document 2: WO2019 / 221193 Summary of the invention
[0012] Problems to be solved by the invention
[0013] Zn-Al-Mg alloy plated steels with high Al and Mg concentrations have superior corrosion resistance compared to Zn-plated steels in areas with severe corrosion environments with high salt content, but they still tend to develop white rust early after construction. In addition, the plating layer with a high Mg concentration is prone to oxidation discoloration, and the hardness of the plating layer sometimes makes the workability poor.
[0014] Therefore, an object of the present disclosure is to provide a plated steel material having excellent corrosion resistance even in a heavily salt-damaged area and capable of achieving both workability and discoloration resistance, and a method for producing the same.
[0015] Means for solving problems
[0016] The above-mentioned problems can be solved by the following means.
[0017] <1> A plated steel material comprises a base steel material and a plated layer, wherein the plated layer comprises a Zn-Al-Mg alloy layer disposed on the surface of the base steel material and a Mg-concentrated layer disposed on the surface of the Zn-Al-Mg alloy layer, wherein:
[0018] The chemical composition of the coating contains, in mass %, the following:
[0019] Zn: more than 65.00%,
[0020] Al: more than 5.00% and less than 25.00%,
[0021] Mg: more than 3.00% and less than 12.50%,
[0022] Sn: 0% to 3.0%,
[0023] Bi: 0% or more and less than 5.00%,
[0024] In: 0% or more and less than 2.00%,
[0025] Ca: 0% to 3.00%,
[0026] Y: 0% to 0.50%,
[0027] La: 0% or more and less than 0.50%,
[0028] Ce: 0% or more and less than 0.50%,
[0029] Si: 0% or more and less than 2.5%,
[0030] Cr: 0% or more and less than 0.25%,
[0031] Ti: 0% or more and less than 0.25%,
[0032] Zr: 0% or more and less than 0.25%,
[0033] Mo: 0% or more and less than 0.25%,
[0034] W: 0% or more and less than 0.25%,
[0035] Ag: 0% or more and less than 0.25%,
[0036] P: 0% or more and less than 0.25%,
[0037] Ni: 0% or more and less than 0.25%,
[0038] Co: 0% or more and less than 0.25%,
[0039] V: 0% or more and less than 0.25%,
[0040] Nb: 0% or more and less than 0.25%,
[0041] Cu: 0% or more and less than 0.25%,
[0042] Mn: 0% or more and less than 0.25%,
[0043] Li: 0% or more and less than 0.25%,
[0044] Na: 0% or more and less than 0.25%,
[0045] K: 0% or more and less than 0.25%,
[0046] Fe: 0% to 5.0%,
[0047] Sr: 0% or more and less than 0.5%,
[0048] Sb: 0% or more and less than 0.5%,
[0049] Pb: 0% or more and less than 0.5%,
[0050] B: 0% or more and less than 0.5%, and
[0051] Impurities,
[0052] The total area ratio of Al crystals, MgZn2 crystals, and Zn / Al / MgZn2 ternary eutectics in the Zn-Al-Mg alloy layer is 90% or more.
[0053] The thickness of the Mg concentrated layer is greater than or equal to 0.8 μm and less than or equal to (plating layer thickness×1 / 2).
[0054] <2> According to the above <1> The plated steel material, wherein the plated layer comprises an Al-Fe alloy layer between the base steel material and the Zn-Al-Mg alloy layer.
[0055] <3> One of the above <1> or <2> The method for manufacturing the plated steel material, wherein:
[0056] The base steel material is immersed in a plating bath, and after the base steel material is lifted out of the plating bath,
[0057] Cooling is performed in the temperature range of 450-395°C at an average cooling rate of less than 15°C / s.
[0058] Cooling is performed in the temperature range of 395 to 340°C at an average cooling rate of less than 3°C / s.
[0059] Cooling is performed in a temperature range of 340 to 280°C at an average cooling rate of 10 to 20°C / s or more.
[0060] After cooling, skin-pass rolling is performed under the conditions that the surface roughness Ra of the skin-pass rolling roller is 1 to 5 μm and the skin-pass rolling pressure is 100 to 500 tons.
[0061] Effects of the Invention
[0062] According to the present disclosure, it is possible to provide a plated steel material having excellent corrosion resistance even in a heavily salt-damaged area and capable of achieving both workability and discoloration resistance, and a method for producing the same. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] Figure 1 This is a graph for explaining a method for measuring the thickness of the Mg concentrated layer. DETAILED DESCRIPTION
[0064] Hereinafter, an example of the present disclosure will be described.
[0065] In addition, in this disclosure, the expression "%" of the content of each element in a chemical composition means "mass %".
[0066] The numerical range expressed using "to" means a range including the numerical values described before and after "to" as the lower limit and the upper limit.
[0067] When “exceeds” or “is lower than” is added to the numerical value described before and after “to”, the numerical range means a range not including these numerical values as the lower limit or the upper limit.
[0068] The content of an element in a chemical composition is sometimes expressed as an element concentration (eg, Zn concentration, Mg concentration, etc.).
[0069] The plated steel material of the present disclosure has a base steel material and a plated layer including a Zn—Al—Mg alloy layer disposed on a surface of the base steel material and a Mg-concentrated layer disposed on a surface of the Zn—Al—Mg alloy layer.
[0070] Moreover, the total area ratio of Al crystals, MgZn2 crystals, and Zn / Al / MgZn2 ternary eutectics in the Zn-Al-Mg alloy layer is greater than 90%.
[0071] Furthermore, the thickness of the Mg concentrated layer is not less than 0.8 μm and not more than (plating layer thickness×1 / 2).
[0072] The plated steel material disclosed in the present invention has a Mg-concentrated layer of the Zn-Al-Mg alloy layer on the surface of the Zn-Al-Mg alloy layer, so a dense corrosion product film containing Mg is formed early in the initial stage of corrosion. The corrosion rate is reduced by the dense corrosion product film. Therefore, the corrosion resistance is excellent even in a heavy salt-damaged area with a severe corrosion environment with high salt content. In addition, by setting the chemical composition of the plating layer and the range of the Mg-concentrated layer in an appropriate range, it is possible to take both processability and discoloration resistance into consideration.
[0073] In addition, by having a Zn-Al-Mg alloy layer having the above structure under the Mg-concentrated layer, it is possible to supply Mg ions and Al ions to the corrosive environment from the middle to the late stage of corrosion while ensuring workability. Thus, the corrosion resistance is improved by maintaining a dense corrosion product film.
[0074] Hereinafter, the plated steel material of the present disclosure will be described in detail.
[0075] (Base steel)
[0076] The shape of the base steel material is not particularly limited. In addition to steel plates, base steel materials include steel pipes, civil engineering materials (fences, corrugated pipes, drainage ditch covers, sand-proof plates, bolts, wire mesh, guardrails, water cutoff walls, etc.), home appliance components (frames of air conditioner outdoor units, etc.), and automobile parts (travel components, etc.). Forming can be performed by various plastic processing methods such as press working, roll forming, and bending.
[0077] The material of the base steel is not particularly limited. Suitable base steels include ordinary steel, pre-plated steel, Al-killed steel, ultra-low carbon steel, high carbon steel, various high-strength steels, and some high-alloy steels (steels containing strengthening elements such as Ni and Cr).
[0078] Base Steel Material There are no particular restrictions on conditions such as the method for producing the base steel material and the method for producing the base steel sheet (hot rolling method, pickling method, cold rolling method, etc.).
[0079] In addition, as the base steel material, a hot-rolled steel sheet, a hot-rolled steel strip, a cold-rolled steel sheet, and a cold-rolled steel strip described in JIS G 3302 (2010) can also be used.
[0080] The base steel material may also be a pre-plated steel material. The pre-plated steel material may be obtained, for example, by an electrolytic treatment method or a displacement plating method. In the electrolytic treatment method, the pre-plated steel material may be obtained by immersing the base steel material in a sulfuric acid bath or a chloride bath containing metal ions of a plurality of pre-plating components and performing electrolytic treatment. In the displacement plating method, the pre-plated steel material may be obtained by immersing the base steel material in an aqueous solution containing metal ions of a plurality of pre-plating components and having a pH adjusted by sulfuric acid, so that metals are precipitated by displacement.
[0081] As the pre-plated steel material, a nickel pre-plated steel material can be cited as a representative example.
[0082] (Plating)
[0083] The plating layer includes a Zn-Al-Mg alloy layer and a Mg-concentrated layer disposed on the surface of the Zn-Al-Mg alloy layer. In addition to the Zn-Al-Mg alloy layer and the Mg-concentrated layer, the plating layer may also include an Al-Fe alloy layer. The Al-Fe alloy layer may be disposed between the base steel material and the Zn-Al-Mg alloy layer.
[0084] That is, the plating layer may be a laminated structure including a Zn-Al-Mg alloy layer, a Mg-concentrated layer, and an Al-Fe alloy layer.
[0085] However, an oxide film of the plating constituent element of about 50 nm may be formed on the plating surface, but it is considered that it does not constitute the main body of the plating relative to the thickness of the entire plating (about 8 to 60 μm).
[0086] The coating weight is preferably 40 to 300 g / m 2 .
[0087] If the coating weight is 40g / m 2 In addition, if the coating weight is 300 g / m 2 If the above conditions are met, it is possible to suppress appearance defects such as sagging patterns of the plating layer.
[0088] Next, the chemical composition of the plating layer will be described.
[0089] The chemical composition of the plating layer is defined as containing, in mass %, the following:
[0090] Zn: more than 65.00%,
[0091] Al: more than 5.00% and less than 25.00%,
[0092] Mg: more than 3.00% and less than 12.50%,
[0093] Sn: 0% to 3.00%,
[0094] Bi: 0% or more and less than 5.00%,
[0095] In: 0% or more and less than 2.00%,
[0096] Ca: 0% to 3.00%,
[0097] Y: 0% to 0.50%,
[0098] La: 0% or more and less than 0.50%,
[0099] Ce: 0% or more and less than 0.50%,
[0100] Si: 0% or more and less than 2.5%,
[0101] Cr: 0% or more and less than 0.25%,
[0102] Ti: 0% or more and less than 0.25%,
[0103] Zr: 0% or more and less than 0.25%,
[0104] Mo: 0% or more and less than 0.25%,
[0105] W: 0% or more and less than 0.25%,
[0106] Ag: 0% or more and less than 0.25%,
[0107] P: 0% or more and less than 0.25%,
[0108] Ni: 0% or more and less than 0.25%,
[0109] Co: 0% or more and less than 0.25%,
[0110] V: 0% or more and less than 0.25%,
[0111] Nb: 0% or more and less than 0.25%,
[0112] Cu: 0% or more and less than 0.25%,
[0113] Mn: 0% or more and less than 0.25%,
[0114] Li: 0% or more and less than 0.25%,
[0115] Na: 0% or more and less than 0.25%,
[0116] K: 0% or more and less than 0.25%,
[0117] Fe: 0% to 5.00%,
[0118] Sr: 0% or more and less than 0.50%,
[0119] Sb: 0% or more and less than 0.50%,
[0120] Pb: 0% or more and less than 0.50%,
[0121] B: 0% or more and less than 0.50%, and
[0122] Impurities.
[0123] In the chemical composition of the plating layer, Sn, Bi, In, Ca, Y, La, Ce, Si, Cr, Ti, Zr, Mo, W, Ag, P, Ni, Co, V, Nb, Cu, Mn, Li, Na, K, Fe, Sr, Sb, Pb and B are optional components. In other words, these elements may not be contained in the plating layer. When these optional components are contained, the content of each optional element is preferably in the range described below.
[0124] Here, the chemical composition of the plating layer is the average chemical composition of the entire plating layer (the average chemical composition of the Zn-Al-Mg alloy layer and the Mg concentrated layer, or the average chemical composition of the Al-Fe alloy layer, the Zn-Al-Mg alloy layer and the Mg concentrated layer).
[0125] Hereinafter, each element of the plating layer will be described.
[0126] Zn: more than 65.00%
[0127] Zn is an element necessary for obtaining corrosion resistance. When the concentration of Zn is considered in terms of atomic composition ratio, Zn should be the main component because the plating layer is composed of elements with low specific gravity such as Al and Mg.
[0128] Therefore, the Zn concentration is set to be higher than 65.00%. The Zn concentration is preferably 70.00% or higher. The upper limit of the Zn concentration is the concentration that does not include the remainder of elements other than Zn and impurities.
[0129] Al: more than 5.00% and less than 25.00%
[0130] Al is an element necessary for forming Al crystals and ensuring corrosion resistance. Al is also an element necessary for improving the adhesion of the plating layer and ensuring workability. Therefore, the lower limit of the Al concentration is set to more than 5.00% (preferably 10.00% or more).
[0131] On the other hand, if the Al concentration increases too much, the corrosion resistance tends to deteriorate. Therefore, the upper limit of the Al concentration is set to less than 25.00% (preferably 23.00% or less).
[0132] Mg: more than 3.00% and less than 12.50%
[0133] Mg is an element necessary for ensuring corrosion resistance. Therefore, the lower limit of the Mg concentration is set to be more than 3.00% (preferably more than 4.00%).
[0134] On the other hand, if the Mg concentration is increased too much, the workability tends to deteriorate. Therefore, the upper limit of the Mg concentration is set to less than 12.50% (preferably 10.00% or less).
[0135] Sn: 0~3.00%
[0136] Sn is an element that contributes to corrosion resistance and initial discoloration resistance. Therefore, the lower limit of the Sn concentration is preferably greater than 0.00% (preferably 0.05% or more, more preferably 0.10% or more).
[0137] On the other hand, if the Sn concentration increases too much, the corrosion resistance and the initial discoloration resistance tend to deteriorate. Therefore, the upper limit of the Sn concentration is made 3.00% or less.
[0138] Bi: 0% or more and less than 5.00%
[0139] Bi is an element that contributes to corrosion resistance. Therefore, the lower limit of the Bi concentration is preferably greater than 0.00% (preferably 0.10% or more, more preferably 3.00% or more).
[0140] On the other hand, if the Bi concentration increases too much, the corrosion resistance tends to deteriorate. Therefore, the upper limit of the Bi concentration is set to less than 5.00% (preferably 4.80% or less).
[0141] In: 0% or more and less than 2.00%
[0142] In is an element that contributes to corrosion resistance. Therefore, the lower limit of the In concentration is preferably greater than 0.00% (preferably 0.10% or more, more preferably 1.00% or more).
[0143] On the other hand, if the In concentration increases too much, the corrosion resistance tends to deteriorate. Therefore, the upper limit of the In concentration is set to less than 2.00% (preferably 1.80% or less).
[0144] Ca: 0%~3.00%
[0145] Ca is an element that can adjust the amount of Mg elution most suitable for imparting corrosion resistance. Therefore, the lower limit of the Ca concentration is preferably more than 0.00% (preferably 0.05% or more).
[0146] On the other hand, if the Ca concentration increases too much, there is a tendency for corrosion resistance and workability to deteriorate. Therefore, the upper limit of the Ca concentration is set to 3.00% or less (preferably 1.00% or less).
[0147] Y: 0%~0.50%
[0148] Y is an element that contributes to corrosion resistance. Therefore, the lower limit of the Y concentration is preferably more than 0.00% (preferably 0.10% or more).
[0149] On the other hand, if the Y concentration increases too much, the corrosion resistance tends to deteriorate. Therefore, the upper limit of the Y concentration is set to 0.50% or less (preferably 0.30% or less).
[0150] La and Ce: 0% or more and less than 0.50%
[0151] La and Ce are elements that contribute to corrosion resistance. Therefore, the lower limits of the La concentration and the Ce concentration are preferably more than 0.00% (preferably 0.10% or more), respectively.
[0152] On the other hand, if the La concentration and the Ce concentration are excessively increased, the corrosion resistance tends to deteriorate. Therefore, the upper limits of the La concentration and the Ce concentration are each set to less than 0.50% (preferably 0.40% or less).
[0153] Si: 0% or more and less than 2.50%
[0154] Si is an element that inhibits the growth of the Al-Fe alloy layer and helps improve corrosion resistance. Therefore, the Si concentration is preferably more than 0.00% (preferably 0.05% or more, more preferably 0.10% or more). In particular, when Sn is not contained (that is, when the Sn concentration is 0%), from the perspective of ensuring corrosion resistance, the Si concentration is preferably 0.10% or more (preferably 0.20% or more).
[0155] On the other hand, if the Si concentration is too high, there is a tendency for corrosion resistance and workability to deteriorate. Therefore, the upper limit of the Si concentration is set to less than 2.50%. In particular, from the viewpoint of corrosion resistance, the Si concentration is preferably 2.40% or less, more preferably 1.80% or less, and further preferably 1.20% or less.
[0156] Cr, Ti, Zr, Mo, W, Ag, P, Ni, Co, V, Nb, Cu, Mn, Li, Na and K: 0% or more and less than 0.25%
[0157] Cr, Ti, Zr, Mo, W, Ag, P, Ni, Co, V, Nb, Cu, Mn, Li, Na, and K are elements that contribute to corrosion resistance. Therefore, the lower limits of the concentrations of Cr, Ti, Zr, Mo, W, Ag, P, Ni, Co, V, Nb, Cu, Mn, Li, Na, and K are preferably more than 0% (preferably 0.05% or more, more preferably 0.10% or more).
[0158] On the other hand, if the concentration of Cr, Ti, Zr, Mo, W, Ag, P, Ni, Co, V, Nb, Cu, Mn, Li, Na, and K increases too much, there is a tendency for corrosion resistance to deteriorate. Therefore, the upper limit of the concentration of Cr, Ti, Zr, Mo, W, Ag, P, Ni, Co, V, Nb, Cu, Mn, Li, Na, and K is set to less than 0.25%. The upper limit of the concentration of Cr, Ti, Zr, Mo, W, Ag, P, Ni, Co, V, Nb, Cu, Mn, Li, Na, and K is preferably 0.22% or less.
[0159] Fe: 0%~5.00%
[0160] When the plating layer is formed by hot-dip plating, the Zn—Al—Mg alloy layer and the Al—Fe alloy layer contain a certain Fe concentration.
[0161] It can be confirmed that even if Fe concentration is up to 5.00% in the plating layer (especially Zn-Al-Mg alloy layer), it will not have a bad effect on performance. Since most of Fe is contained in the Al-Fe alloy layer, if the thickness of this layer is thick, the Fe concentration usually increases.
[0162] Sr, Sb, Pb and B: 0% or more and less than 0.50%
[0163] Sr, Sb, Pb and B are elements that contribute to corrosion resistance. Therefore, the lower limits of the concentrations of Sr, Sb, Pb and B are preferably more than 0% (preferably 0.05% or more, more preferably 0.10% or more).
[0164] On the other hand, if the concentrations of Sr, Sb, Pb, and B are excessively increased, the corrosion resistance tends to deteriorate. Therefore, the upper limit values of the concentrations of Sr, Sb, Pb, and B are each set to less than 0.50%.
[0165] Impurities
[0166] Impurities are components contained in the raw materials or mixed in during the manufacturing process, and are components that are not intentionally contained. For example, components other than Fe may be mixed into the plating layer as impurities in trace amounts due to mutual atomic diffusion between the base steel material and the plating bath.
[0167] The chemical composition of the coating can be determined by the following method.
[0168] First, the coating is stripped and dissolved with an acid containing a corrosion inhibitor that inhibits corrosion of the base steel to obtain an acid solution. Next, the obtained acid solution is measured by ICP analysis, thereby obtaining the chemical composition of the coating. The acid type is not particularly limited as long as it can dissolve the coating. Furthermore, the chemical composition can be measured as an average chemical composition. Furthermore, in ICP analysis, the Zn concentration can be calculated according to the "formula: Zn concentration = 100% - other element concentrations (%)".
[0169] When a pre-plated steel material is used as the base steel material, the components of the pre-plating are also detected.
[0170] For example, when using pre-nickel-plated steel, the ICP analysis detects not only the Ni in the plating layer but also the Ni in the pre-nickel plating. 2 ~3g / m 2 When a pre-plated steel material (thickness of about 0.1 to 0.3 μm) is used as the base steel material, even if the Ni concentration contained in the plating layer is 0%, the Ni concentration is detected at 0.1 to 15% when measured by ICP analysis.
[0171] Among them, the method of judging whether the base steel material is a pre-nickel plated steel material is as follows.
[0172] From the steel material to be measured, a sample is collected with the cross section cut along the coating thickness direction as the measurement surface.
[0173] For the measurement surface of the sample, the Ni concentration is measured by line analysis near the interface between the coating and the base steel in the steel by an electron probe microanalyzer (Electron Probe MicroAnalyser: FE-EPMA). The measurement conditions are acceleration voltage: 15kV, beam diameter: about 100nm, irradiation time per point: 1000ms, and measurement interval: 60nm. Furthermore, the measurement distance can be any distance that can confirm whether the Ni concentration is concentrated at the interface between the coating and the base steel in the steel.
[0174] Furthermore, as long as the Ni concentration is concentrated at the interface between the plating layer and the base steel in the steel, the base steel is identified as a pre-nickel plated steel.
[0175] When a nickel-pre-plated steel material is used as the base steel material, the Ni concentration of the plating layer is defined as a value measured by the following method.
[0176] First, the luminescence intensity of Ni was measured for three or more standard samples with different Ni concentrations (Zn alloy standard samples IMN ZH1, ZH2, and ZH4 manufactured by BAS) using a high-frequency glow discharge emission surface analyzer (GDS: manufactured by Horiba, Ltd., model: GD-Profiler2). A calibration curve was prepared based on the relationship between the obtained Ni luminescence intensity and the Ni concentration of the standard sample.
[0177] Next, the plated surface of the sample is polished in the plated thickness direction (hereinafter also referred to as "Z-axis direction").
[0178] Specifically, after dry-grinding the surface of the coating with #1200 abrasive paper, fine grinding was performed using a fine polishing solution containing aluminum oxide with an average particle size of 3 μm, a fine polishing solution containing aluminum oxide with an average particle size of 1 μm, and a fine polishing solution containing colloidal silica, respectively.
[0179] Furthermore, the Zn intensity of the surface of the plated layer was measured by XRF (fluorescent X-ray analysis) before and after polishing, and the time when the Zn intensity after polishing reached 1 / 2 of the Zn intensity before polishing was defined as 1 / 2 of the layer thickness of the plated layer.
[0180] Next, the luminescence intensity of Ni at the 1 / 2 position of the coating film thickness of the plated steel material to be measured was measured by a high-frequency glow discharge emission surface analyzer (GDS: manufactured by Horiba, Ltd., model: GD-Profiler2). The Ni concentration at the 1 / 2 position of the coating layer was obtained from the obtained Ni luminescence intensity and the prepared calibration curve.
[0181] When a nickel-preplated steel material is used as the base steel material, the Zn concentration of the plating layer is defined as the Zn concentration calculated from the following formula.
[0182] Formula: Zn concentration = 100 - (Zn and other element concentrations other than Ni obtained by ICP analysis + Ni concentration obtained by GDS)
[0183] Furthermore, the measurement conditions of the high-frequency glow discharge emission surface analysis device were set as follows:
[0184] HV: 630V
[0185] Anode diameter: φ4mm
[0186] Gas: Ar
[0187] Gas pressure: 600Pa
[0188] Power: 35W
[0189] Next, the structure of the Zn—Al—Mg alloy layer will be described.
[0190] The total area ratio of Al crystals, MgZn2 crystals, and Zn / Al / MgZn2 ternary eutectics in the Zn-Al-Mg alloy layer is 90% or more.
[0191] From the viewpoint of improving corrosion resistance, the lower limit of the area ratio is preferably 92%, 95%, or 98%, and is particularly preferably 100%.
[0192] In addition, the area ratio of the structure other than the above-mentioned Al crystal, MgZn2 crystal, and Zn / Al / MgZn2 ternary eutectic, such as Zn crystal, is preferably 0 to 10%, more preferably 0 to 8%, 0 to 5%, and further preferably 0 to 2%. The area ratio of Zn crystal is particularly preferably 0% (that is, it is particularly preferred that Zn crystal is not contained).
[0193] Here, the Al crystal and the Zn crystal refer to crystals that are independently crystallized.
[0194] The structure of the Zn-Al-Mg alloy layer can be measured by the following method.
[0195] First, a sample is collected from the plated steel material to be measured. However, the sample may be collected from a place without a plating defect other than the vicinity of the punched end surface of the plated steel material (2 mm from the end surface).
[0196] Next, the plated surface of the sample is polished in the plated thickness direction (hereinafter also referred to as "Z-axis direction").
[0197] Specifically, after dry-grinding the surface of the coating with #1200 abrasive paper, fine grinding was performed using a fine polishing solution containing aluminum oxide with an average particle size of 3 μm, a fine polishing solution containing aluminum oxide with an average particle size of 1 μm, and a fine polishing solution containing colloidal silica, respectively.
[0198] In addition, before and after grinding, the Zn intensity of the coating surface is measured by XRF (fluorescent X-ray analysis), and the Zn intensity after grinding becomes 1 / 2 of the Zn intensity before grinding as 1 / 2 of the coating thickness. Since the Zn-Al-Mg alloy layer occupies more than 1 / 2 of the coating thickness, the grinding surface of the coating surface ground to 1 / 2 of the thickness becomes the grinding surface of the Zn-Al-Mg alloy layer. Therefore, by analyzing the grinding surface, the metal structure contained in the Zn-Al-Mg alloy layer can be grasped.
[0199] Next, the polished surface was observed by scanning electron microscopy (SEM) at a magnification of 500 times to obtain a backscattered electron image (hereinafter also referred to as "SEM backscattered electron image"). The SEM observation conditions were set to acceleration voltage: 15 kV, irradiation current: 10 nA, and field size: 244 μm×198 μm.
[0200] In addition, an electron probe microanalyzer (FE-EPMA) was used, and the conditions were set to acceleration voltage: 15kV, irradiation current: 30nA, beam diameter: about 100nm, irradiation time per point: 5ms, and measurement interval: 300nm, and mapping analysis was performed at a magnification of 500 times. As a result, it can be roughly divided into an area where the detection parts of Mg and Zn overlap, an area where the detection parts of Al and Zn overlap, and an area where Zn is detected alone. At this time, the area where the detection parts of Mg and Zn overlap is regarded as MgZn2, and the area where the detection parts of Al and Zn overlap is regarded as Al crystal. In addition, in the area where Zn is detected alone, FE-EPMA line analysis is performed at a magnification of 2000 times over a length of 10μm. At this time, in the measurement area, the area where Mg or Al is detected at more than 1% can be distinguished as Zn / Al / MgZn2 ternary eutectic, and the area where only Mg and Al are detected at less than 1% can be distinguished as Zn crystal. By subjecting these regions to computer image processing, the area ratio can be obtained (the area (pixel) of each phase in the field of view is calculated).
[0201] Next, the Mg concentrated layer will be described.
[0202] The Mg-concentrated layer is a layer in which the Mg concentration is concentrated due to densification of Mg-containing phases such as Zn / Al / MgZn2 ternary eutectic existing in the surface layer of the Zn-Al-Mg alloy layer.
[0203] If the Mg concentrated layer is thin, the corrosion resistance is inferior. On the other hand, if the Mg concentrated layer is too thick, the discoloration resistance is deteriorated.
[0204] Therefore, the thickness of the Mg concentrated layer is set to 0.8 μm or more and (plating layer thickness×1 / 2) or less. The thickness of the Mg concentrated layer is preferably 0.9 μm or more and 25 μm or less, and more preferably 1.0 μm or more and 22.5 μm or less.
[0205] The plating thickness is preferably 5 μm or more and 50 μm or less, and more preferably 10 μm or more and 45 μm or less.
[0206] The Mg concentrated layer is a layer defined as follows.
[0207] First, the intensity distribution of the elements (Zn, Al, Mg, Fe, etc.) contained in each coating layer was measured by sputtering in the depth direction from the surface side of the coating layer by glow discharge spectrometry (quantitative GDS) (refer to Figure 1 )(Measurement equipment: manufactured by Horiba, Ltd., model: GD-Profiler2, measurement conditions: DC mode, voltage 900V, current 20mA). At this time, when a chemical conversion treatment film or the like is present on the coating layer, the depth distribution of the intensity of the element that is the main component of the film (for example, carbon (C) in the case of an organic film, and the element that is the main component in the case of an inorganic film) is also measured. In addition, in the case of an inorganic film, the so-called element that is the main component is, for example, zirconium (Zr) in the case of a zirconium oxide film, and silicon (Si) in the case of a film containing a silane coupling agent.
[0208] The measurement is carried out until the plating layer disappears and the depth of the substrate is fully exposed. At this time, the depth of the hole after the measurement [μm] is measured, and the sputtering rate [μm / s] can be obtained by dividing the value by the GDS measurement time [s]. If the sputtering rate is multiplied by the elapsed time from the start of the measurement at the target measurement position, the depth [μm] from the surface of the target measurement position can be obtained.
[0209] Among them, when the intensity change of Fe is seen from the direction of the coating surface, the point where the intensity increase of Fe per 0.1μm exceeds 0.003 is defined as (A). The intensity of Mg in the above point (A) is set to 1, and the point (B) where the relative intensity of Mg is 1.03 when the Mg intensity is seen from the substrate (i.e., substrate steel material) side to the coating surface side is defined as the interface between the Mg concentrated layer and the Zn-Al-Mg alloy layer. When the coating surface side is viewed from this point, the point (C) where the intensity of Mg and the intensity of carbon (C) are the same is regarded as the upper end of the Mg concentrated layer. In addition, the intensity of carbon (C) that determines point (C) (the intensity of carbon (C) when there is no chemical conversion treatment film, etc. on the coating) is the intensity of carbon (C) derived from dust or oil attached to the coating surface.
[0210] However, when a chemical conversion film or the like exists on the plated layer, a point having the same intensity as the element constituting the main component of the film is set as point (C) as the upper end of the Mg concentrated layer.
[0211] The Mg-concentrated layer is defined as a layer between point (B) and point (C), and the thickness of the Mg-concentrated layer is defined as the average value of the difference in depth between point (B) and point (C) measured at three locations.
[0212] Next, the Al—Fe alloy layer will be described.
[0213] The Al-Fe alloy layer is sometimes formed on the surface of the base steel material (specifically, between the base steel material and the Zn-Al-Mg alloy layer), and is a layer whose main phase is the Al5Fe phase as a structure. The Al-Fe alloy layer is formed by mutual atomic diffusion of the base steel material and the plating bath. Since the steel material disclosed in the present invention forms the plating layer by hot-dip plating, it is easy to form an Al-Fe alloy layer in the plating layer containing the Al element. Since the plating bath contains Al above a certain concentration, the Al5Fe phase is formed most. However, atomic diffusion takes time, and in addition, there are parts with increased Fe concentration in the parts close to the base steel material. Therefore, the Al-Fe alloy layer sometimes contains a small amount of AlFe phase, Al3Fe phase, Al5Fe2 phase, etc. locally. In addition, since Zn is also contained in a certain concentration in the plating bath, the Al-Fe alloy layer also contains a small amount of Zn.
[0214] In terms of corrosion resistance, there is no significant difference among the Al5Fe phase, Al3Fe phase, AlFe phase and Al5Fe2 phase. The corrosion resistance mentioned here refers to the corrosion resistance in the part not affected by welding.
[0215] Among them, when Si is contained in the plating layer, Si is particularly easy to enter the Al-Fe alloy layer, and sometimes it becomes an Al-Fe-Si intermetallic compound phase. The intermetallic compound phase to be identified is the AlFeSi phase, and as isomers, there are α, β, q1, q2-AlFeSi phases, etc. Therefore, these AlFeSi phases can sometimes be detected in the Al-Fe alloy layer. The Al-Fe alloy layer containing these AlFeSi phases is also called the Al-Fe-Si alloy layer.
[0216] Furthermore, since the Al—Fe—Si alloy layer is thinner than the Zn—Al—Mg alloy layer, the influence on the corrosion resistance of the entire plating layer is also small.
[0217] In addition, when various pre-plated steel materials are used as the base steel material, the structure of the Al-Fe alloy layer sometimes changes with the difference in the amount of pre-plating. Specifically, there are the following situations: a pure metal layer used for pre-plating remains around the Al-Fe alloy layer; an intermetallic compound phase (such as Al3Ni phase) formed by combining the constituent components of the Zn-Al-Mg alloy layer and the pre-plating components forms an alloy layer; an Al-Fe alloy layer is formed by replacing a part of Al atoms and Fe atoms; or an Al-Fe-Si alloy layer is formed by replacing a part of Al atoms, Fe atoms and Si atoms.
[0218] That is, the so-called Al—Fe alloy layer is a layer including the alloy layers in various forms described above in addition to the alloy layer mainly composed of the Al 5 Fe phase.
[0219] In addition, among various pre-plated steel materials, when a plating layer is formed on a pre-nickel plated steel material, an Al-Ni-Fe alloy layer can be formed as the Al-Fe alloy layer.
[0220] The thickness of the Al—Fe alloy layer is, for example, not less than 0 μm and not more than 7 μm.
[0221] The thickness of the Al—Fe alloy layer is preferably 0.05 μm or more and 5 μm or less from the viewpoint of improving the adhesion of the plating layer (specifically, the Zn—Al—Mg alloy layer) and ensuring corrosion resistance and workability.
[0222] Generally, the thickness of the Zn-Al-Mg alloy layer is thicker than that of the Al-Fe alloy layer, so the contribution of the Al-Fe alloy layer to the corrosion resistance of the plated steel is smaller than that of the Zn-Al-Mg alloy layer. However, as can be inferred from the results of component analysis, the Al-Fe alloy layer contains corrosion-resistant elements, namely Al and Zn, at a certain concentration or above. Therefore, the Al-Fe alloy layer has a certain degree of corrosion resistance to the base steel.
[0223] Furthermore, when a plating layer having the chemical composition specified in the present disclosure is formed by hot-dip plating, an Al-Fe alloy layer having a thickness of 100 nm or more is often formed between the base steel material and the Zn-Al-Mg alloy layer.
[0224] From the perspective of corrosion resistance, the thicker the Al-Fe alloy layer, the better. Therefore, the thickness of the Al-Fe alloy layer is preferably 0.05 μm or more. However, a thick Al-Fe alloy layer causes a significant deterioration in processability, so the thickness of the Al-Fe alloy layer is preferably 7 μm or less. If the thickness of the Al-Fe alloy layer is 7 μm or less, the amount of cracks and powdering occurring starting from the Al-Fe alloy layer is reduced, and processability is improved. The thickness of the Al-Fe alloy layer is more preferably 5 μm or less, and further preferably 2 μm or less.
[0225] The thickness of the Al-Fe alloy layer can be measured by the following method.
[0226] After the sample is embedded in the resin and then ground, the thickness of the identified Al-Fe alloy layer is measured at any five locations in the SEM backscattered electron image of the coating cross section (the cross section along the thickness direction of the coating) (where the field of view is set to be a field of view where the Al-Fe alloy layer can be seen at a magnification of 10,000 times and a field of view size of 50 μm wide × 200 μm long). Then, the arithmetic average of the five locations is taken as the thickness of the Al-Fe alloy layer.
[0227] In addition, regarding the plating thickness, the thickness was measured at any five locations in the cross-sectional SEM backscattered electron image (where the magnification was 500 times and the viewing field size was 198 μm wide × 244 μm long so that the entire plating layer could be seen). Then, the arithmetic average of the five locations was taken as the plating thickness.
[0228] (Method for producing plated steel material)
[0229] Hereinafter, an example of the method for producing the plated steel material of the present disclosure will be described.
[0230] The plated steel material disclosed herein can be obtained by forming a plating layer having the above-specified chemical composition and metal structure on the surface (ie, one side or both sides) of a base steel material (base steel plate, etc.) by hot-dip plating.
[0231] Specifically, as an example, hot dip treatment is performed under the following conditions. Hereinafter, as an example of the method for producing a plated steel material of the present disclosure, a method for producing a plated steel sheet will be described.
[0232] First, a base steel sheet as a base steel material is immersed in a coating bath, and after being pulled out of the coating bath, the base steel sheet is cooled in a temperature range of 450 to 395° C. at an average cooling rate of 15° C. / s or less.
[0233] Next, cooling is performed in a temperature range of 395 to 340° C. at an average cooling rate of 3° C. / s or less.
[0234] Then, cooling is performed in a temperature range of 340 to 280° C. at an average cooling rate of 10 to 20° C. / s or more.
[0235] Here, the plating is performed by a continuous hot-dip metal plating method such as the Sendzimir method.
[0236] Then, after cooling, skin-pass rolling is performed under the conditions that the surface roughness Ra of the skin-pass rolling roll is 1 to 5 μm and the skin-pass rolling reduction force is 100 to 500 tons.
[0237] Here, the coating solidifies in the order of Al crystals, MgZn2 crystals crystallized around the Al crystals, and Zn / Al / MgZn2 ternary eutectic.
[0238] Therefore, by cooling in the temperature range of 450 to 395°C at an average cooling rate of less than 15°C / s, Al crystals can be grown. Then, by cooling in the temperature range of 395 to 340°C at an average cooling rate of less than 3°C / s, MgZn2 crystals can be reliably crystallized around the Al crystals. Thus, the Zn / Al / MgZn2 ternary eutectic can be refined.
[0239] The upper limit of the average cooling rate in the temperature range of 450 to 395°C is 15°C / s, preferably 13°C / s, and more preferably 11°C / s. The lower limit is not particularly limited, but is preferably 1°C / s, and more preferably 2°C / s or more from the viewpoint of productivity.
[0240] If the average cooling rate in the temperature range of 450 to 395°C exceeds 15°C / s, the Al crystals are too finely crystallized and the Zn / Al / MgZn2 ternary eutectic is excessively finely refined. This makes it difficult to form a Mg-concentrated layer by skin-pass rolling described later.
[0241] The upper limit of the average cooling rate in the temperature range of 395°C to 340°C is 3°C / s, preferably 2.5°C / s. The lower limit is not particularly limited, but is preferably 0.5°C / s, more preferably 1°C / s or more from the viewpoint of productivity.
[0242] In addition, if the average cooling rate in the temperature range of 395°C to 340°C exceeds 3°C / s, the MgZn2 crystals around the Al crystals cannot be fully grown, and the refinement of the Zn / Al / MgZn2 ternary eutectic becomes insufficient. As a result, the Mg-concentrated layer based on the skin-pass rolling described later becomes difficult to form.
[0243] Next, the Zn / Al / MgZn2 ternary eutectic is refined by cooling at an average cooling rate of 10°C / s or more in a temperature range of 340 to 280°C. This makes it easier to form a Mg-concentrated layer by skin pass rolling described later.
[0244] However, if the average cooling rate in the temperature range of 340 to 280°C exceeds 20°C / s, the Zn / Al / MgZn2 ternary eutectic becomes excessively refined, and the Mg-concentrated layer by skin pass rolling described later becomes difficult to form.
[0245] The average cooling rate in the temperature range below 280°C is not limited. For example, furnace cooling may be adopted, or heat preservation may be performed for the purpose of adjusting the quality of the steel. In addition, water cooling may be implemented by spray cooling or the like. The average cooling rate in the method exemplified here is, for example, 50°C / sec or less.
[0246] Next, after cooling, skin smooth rolling is carried out under the conditions that the surface roughness Ra of the skin smooth rolling roller is above 1 μm and the skin smooth rolling reduction force is above 100 tons. The soft Mg-containing crystals (Zn / Al / MgZn2 ternary eutectic, etc.) existing in the surface layer of the Zn-Al-Mg alloy layer are extended to form a Mg concentrated layer.
[0247] However, if the surface roughness Ra of the skin-pass rolling roller exceeds 5 μm, the Mg-concentrated layer becomes too thick due to the increase in the surface area of the plated layer, and the discoloration resistance is deteriorated. On the other hand, if the surface roughness Ra of the skin-pass rolling roller is less than 1 μm, the base steel sheet slips during skin-pass rolling and the rolling cannot be uniformly performed, and the corrosion resistance and discoloration resistance cannot be guaranteed.
[0248] In addition, if the skin-pass rolling pressure exceeds 500 tons, the soft Mg-containing crystals (Zn / Al / MgZn2 ternary eutectic, etc.) are too extended, and the Mg-concentrated layer is difficult to thicken, which deteriorates the corrosion resistance. On the other hand, even if the skin-pass rolling pressure is less than 100 tons, the Mg-concentrated layer is difficult to thicken, which also deteriorates the corrosion resistance.
[0249] In addition, if the skin-pass rolling pressure is within an appropriate range and the surface roughness Ra of the skin-pass rolling roll increases, Figure 1 The point (B) in FIG. 1 tends to move to the right, and the thickness of the Mg-concentrated layer increases.
[0250] The surface roughness Ra of the skin-pass roller can be measured by the following method: The surface roughness of the skin-pass roller is measured at three locations in the width direction of the roller using a stylus-type portable roughness meter, and the average value is taken.
[0251] Hereinafter, post-treatment of the plated steel material that can be used in the present disclosure will be described.
[0252] The plated steel material disclosed in the present invention may also form a film on the plated layer. The film may be formed into one layer or two or more layers. As the type of the film directly above the plated layer, for example, a chromate film, a phosphate film, and a chromate-free film may be listed. The chromate treatment, phosphate treatment, and chromate-free treatment for forming these films may be performed by known methods.
[0253] Chromate treatment includes electrolytic chromate treatment in which a chromate film is formed by electrolysis; reactive chromate treatment in which a film is formed by reaction with a raw material and then the remaining treatment liquid is washed away; and coating chromate treatment in which a treatment liquid is applied to the object to be coated and a film is formed by drying without washing with water. Any of these treatments may be used.
[0254] As the electrolytic chromate treatment, there can be exemplified an electrolytic chromate treatment using chromic acid, silica sol, resin (acrylic resin, vinyl ester resin, vinyl acetate acrylic emulsion, carboxylated styrene butadiene latex, diisopropanolamine-modified epoxy resin, etc.), and hard silica.
[0255] Examples of the phosphate treatment include zinc phosphate treatment, calcium zinc phosphate treatment, and manganese phosphate treatment.
[0256] Chromate-free treatment is particularly suitable because it has no load on the environment. Chromate-free treatment includes electrolytic chromate-free treatment that forms a chromate-free film by electrolysis; reactive chromate-free treatment that forms a film by reaction with the raw material and then rinses the remaining treatment liquid; and coating chromate-free treatment that forms a film by applying the treatment liquid to the object to be coated and drying it without washing with water. Any of these treatments can be used.
[0257] In addition, one or more layers of organic resin films may be provided on the film directly above the coating. The organic resin is not limited to a specific type, and for example, polyester resin, polyurethane resin, epoxy resin, acrylic resin, polyolefin resin or modified forms of these resins may be cited. The so-called modified form here refers to a resin in which the reactive functional groups contained in the structures of these resins react with other compounds (monomers and crosslinking agents, etc.) having functional groups that can react with the functional groups in the structures.
[0258] As such an organic resin, one or more organic resins (unmodified) may be mixed and used, or one or more organic resins obtained by modifying at least one other organic resin in the presence of at least one organic resin may be mixed and used. In addition, the organic resin film may contain any coloring pigment and rust-proof pigment. A water-based material may also be used by dissolving or dispersing in water.
[0259] Example
[0260] (Example)
[0261] In order to obtain the coating layers having the chemical compositions shown in Tables 1 and 2, a predetermined amount of pure metal ingots were used, the ingots were melted in a vacuum melting furnace, and then a coating bath was prepared in the atmosphere. A hot dip plating simulator was used for the preparation of the plated steel sheets.
[0262] As the base steel material, a common hot-rolled steel sheet (C concentration < 0.1%) with a thickness of 2.3 mm was used. The surface to be plated of the base steel material was polished with a brush, and then degreased and pickled before the plating step.
[0263] In one example, as the base steel material, a pre-nickel plated steel material was used, in which a common hot-rolled steel sheet with a thickness of 2.3 mm was pre-nickel plated. The Ni deposition amount was set to 1 g / m 2 ~3g / m 2 In addition, the example using the nickel-pre-plated steel material as the base steel material is indicated as "nickel-pre-plated" in the "base steel material" column in the table.
[0264] A contact type K thermocouple is installed on the back side of the plated surface of the base steel material in order to monitor the temperature of the steel material during the plated steel sheet manufacturing process.
[0265] In all samples, the same reduction treatment method was applied to the base steel material until the process of immersion in the coating bath. That is, in an N2-H2 (5%) environment (dew point below -40°C, oxygen concentration below 25ppm), the base steel material was heated from room temperature to 800°C by electric heating, maintained for 60 seconds, cooled to the coating bath temperature + 10°C by blowing N2 gas, and then immediately immersed in the coating bath.
[0266] In addition, the immersion time in the coating bath of all the plated steel sheets was set to the time in the table. The plated steel sheets were produced so that the coating thickness was 30 μm (±1 μm) by adjusting the N 2 gas friction contact pressure.
[0267] The plating bath temperature was set to 500° C. The plating bath immersion time was set to 2 seconds.
[0268] Then, after the base steel material is pulled out of the coating bath, a coating layer is obtained by a cooling step in which the average cooling rates in the first to third stages shown in Tables 1 and 2 are set to the conditions shown in Tables 1 and 2.
[0269] · Average cooling rate in the first stage: Average cooling rate in the temperature range of 450 to 395°C
[0270] · Average cooling rate in the second stage: Average cooling rate in the temperature range of 395 to 340°C
[0271] · Average cooling rate in the third stage: Average cooling rate in the temperature range of 340 to 280°C
[0272] In addition, in the cooling process, the steel material is cooled by blowing N2 gas to the plated steel material. At this time, in order to achieve a predetermined cooling rate in the above-mentioned temperature range, cooling is performed while adjusting the blowing amount of N2 gas.
[0273] - Various measurements -
[0274] A sample was cut out from the obtained plated steel sheet and the following items were measured according to the above-mentioned method.
[0275] Coating thickness
[0276] Thickness of Mg concentration layer
[0277] ·Thickness of the Al-Fe alloy layer (In the case where a pre-nickel plated steel sheet is used as the base steel material, this indicates the thickness of the Al-Ni-Fe alloy layer)
[0278] Total area ratio of Al crystals, MgZn2 crystals, and Zn / Al / MgZn2 ternary eutectic in the Zn-Al-Mg alloy layer (in the table, marked as specific structure area ratio)
[0279] -Corrosion resistance-
[0280] Samples were cut from the obtained plated steel sheets. The samples were then arranged longitudinally and subjected to 21 cycles of a combined cycle corrosion test (CCT) according to the corrosion acceleration test (JASO M609-91). After the corrosion test, the corrosion loss was 20 g / m 2 The following cases are rated as "A" and will exceed 20g / m 2 The situation is evaluated as "NG".
[0281] -Processability-
[0282] A sample was cut from the obtained plated steel sheet. Then, after bending the sample 1T, the processed part was peeled off with a tape, and the area ratio of the plated layer attached to the tape was evaluated. The area ratio of the attached plated layer was evaluated as "A" when it was 5% or less, and "NG" when it exceeded 5%.
[0283] -Discoloration resistance-
[0284] A sample was cut from the obtained plated steel sheet. Then, the sample was hung at an angle of 60° relative to the horizontal direction in a constant temperature and humidity tester (KCL-2000 manufactured by EYELA) at 50°C and 80%RH, and the color difference ΔE after 3 days was evaluated. Regarding the color difference, the L value, a* value, and b* value of the sample in the SCE (specular reflection exclusion) method were measured before and after the test using a colorimeter (CR-400 manufactured by Konica Minolta Optics), and the color difference ΔE was investigated at 4 locations to obtain the average value.
[0285] The average value of the color difference ΔE after 3 days was evaluated as “A” when it was 10 or less, and as “NG” when it exceeded 10.
[0286] The examples are listed in Tables 1 and 2.
[0287] Table 1-1
[0288]
[0289] Table 1-2
[0290]
[0291] Table 1-3
[0292]
[0293] Table 1-4
[0294]
[0295] Table 2-1
[0296]
[0297] Table 2-2
[0298]
[0299] Table 2-3
[0300]
[0301] Table 2-4
[0302]
[0303] The above results show that the plated steel materials of the present disclosure have excellent corrosion resistance even in coastal areas with a severe corrosion environment with high salt content, as compared with the comparative examples. In addition, it is also found that the workability and discoloration resistance are excellent.
[0304] In Test No. 103, since uniform rolling could not be performed and the appearance varied greatly, various plating thicknesses were not measured.
[0305] The preferred implementation modes and embodiments of the present disclosure are described in detail above with reference to the accompanying drawings, but the present disclosure is not limited to such examples. Anyone with ordinary knowledge in the technical field to which the present disclosure belongs can obviously think of various variations or modifications within the scope of the technical ideas described in the claims, and these can of course be understood to also belong to the technical scope of the present disclosure.
[0306] In addition, the entire disclosure of Japanese Patent Application No. 2022-138732 is incorporated herein by reference.
[0307] All documents, patent applications, and technical specifications described in this specification are incorporated herein by reference to the same extent as if each individual document, patent application, or technical specification was specifically and individually indicated to be incorporated by reference.
Claims
1. A plated steel material comprising a base steel material and a plated layer, wherein the plated layer comprises a Zn-Al-Mg alloy layer disposed on a surface of the base steel material and a Mg-concentrated layer disposed on a surface of the Zn-Al-Mg alloy layer, wherein: The chemical composition of the coating contains, in mass %, the following: Zn: more than 65.00%, Al: more than 5.00% and less than 25.00%, Mg: more than 3.00% and less than 12.50%, Sn: 0% to 3.00%, Bi: 0% or more and less than 5.00%, In: 0% or more and less than 2.00%, Ca: 0% to 3.00%, Y:0%~0.50%、 La: 0% or more and less than 0.50%, Ce: 0% or more and less than 0.50%, Si: 0% or more and less than 2.5%, Cr: 0% or more and less than 0.25%, Ti: 0% or more and less than 0.25%, Zr: 0% or more and less than 0.25%, Mo: 0% or more and less than 0.25%, W: 0% or more and less than 0.25%, Ag: 0% or more and less than 0.25%, P: 0% or more and less than 0.25%, Ni: 0% or more and less than 0.25%, Co: 0% or more and less than 0.25%, V: 0% or more and less than 0.25%, Nb: 0% or more and less than 0.25%, Cu: 0% or more and less than 0.25%, Mn: 0% or more and less than 0.25%, Li: 0% or more and less than 0.25%, Na: 0% or more and less than 0.25%, K: 0% or more and less than 0.25%, Fe: 0% to 5.00%, Sr: 0% or more and less than 0.50%, Sb: 0% or more and less than 0.50%, Pb: 0% or more and less than 0.50%, B: 0% or more and less than 0.50%, and Impurities, The total area ratio of Al crystals, MgZn2 crystals, and Zn / Al / MgZn2 ternary eutectics in the Zn-Al-Mg alloy layer is 90% or more. The thickness of the Mg concentrated layer is greater than or equal to 0.8 μm and less than or equal to (plating layer thickness×1 / 2).
2. The plated steel material according to claim 1, wherein: The plating layer includes an Al—Fe alloy layer between the base steel material and the Zn—Al—Mg alloy layer.
3. A method for producing a plated steel material according to claim 1 or 2, wherein: The base steel material is immersed in a plating bath, and after the base steel material is lifted out of the plating bath, Cooling is performed in the temperature range of 450-395°C at an average cooling rate of less than 15°C / s. Cooling is performed in the temperature range of 395 to 340°C at an average cooling rate of less than 3°C / s. Cooling is performed in a temperature range of 340 to 280°C at an average cooling rate of 10 to 20°C / s or more. After cooling, skin-pass rolling is performed under the conditions that the surface roughness Ra of the skin-pass rolling roller is 1 to 5 μm and the skin-pass rolling pressure is 100 to 500 tons.
Citation Information
Patent Citations
Hot dip zn-al-mg-si plated steel excellent in surface property and its production method
JP2001355053A
Inkjet recording device and intermediate connector to be applied to the same
JP2022138732A
Plated steel material
WO2019221193A1
Plated steel material having excellent friction resistance and white rust resistance and method for preparing same
CN108474093A
Plated steel material
CN110191973A